2010
DOI: 10.1002/rmv.655
|View full text |Cite
|
Sign up to set email alerts
|

Review of cytomegalovirus seroprevalence and demographic characteristics associated with infection

Abstract: Cytomegalovirus establishes a lifelong latent infection following primary infection that can periodically reactivate with shedding of infectious virus. Primary infection, reactivation and reinfection during pregnancy can all lead to in utero transmission to the developing fetus. Congenital CMV infections are a major cause of permanent hearing loss and neurological impairment. In this literature review, we found that CMV infection was relatively common among women of reproductive age, with seroprevalence rangin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

52
979
5
37

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,282 publications
(1,073 citation statements)
references
References 133 publications
52
979
5
37
Order By: Relevance
“…Moreover, no difference was found between age and CMV serostatus in the confirmation cohort, which suggests that a potential protective effect of CMV infection on the diagnosis of B‐CLL is unlikely. This discrepancy between the two cohorts in relation to age and CMV serostatus is likely to reflect the different geographical locations of the two cohorts, as the timing of primary exposure to CMV is known to vary dramatically depending on geographical and socio‐economic factors 27.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, no difference was found between age and CMV serostatus in the confirmation cohort, which suggests that a potential protective effect of CMV infection on the diagnosis of B‐CLL is unlikely. This discrepancy between the two cohorts in relation to age and CMV serostatus is likely to reflect the different geographical locations of the two cohorts, as the timing of primary exposure to CMV is known to vary dramatically depending on geographical and socio‐economic factors 27.…”
Section: Discussionmentioning
confidence: 99%
“…African American adults have been found to have twice the prevalence of CMV infection compared with age-matched whites, 35,36 and the rate of CMV seropositivity may approach 100% in some series. 37,38 The reasons for the increased rate of CMV infections among African Americans compared with whites is not completely known, but demographic factors such as African American race, female gender and lower socioeconomic Racial differences in Allo-HCT BK Hamilton et al status have been suggested to be the markers for behaviors and environmental factors that facilitate CMV transmission, such as breast-feeding, childcare practices, sexual activity, larger family sizes or crowded living conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital cytomegalovirus (CMV) infection is the leading infectious cause of developmental and neurologic disabilities and sensorineural hearing loss (SNHL) in children. [1][2][3][4][5] In France, congenital CMV infection currently affects 0.5% of all newborns. 6 Clinical signs in neonates are variable: 5% to 10% are symptomatic at birth, with a mortality rate of up to 10%.…”
Section: What This Study Addsmentioning
confidence: 99%